2008
DOI: 10.1016/j.econlet.2008.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Toward a bias corrected currency equivalent index

Abstract: Measuring the economic stock of money, de ned to be the present value of current and future monetary service ows, is a di cult asset pricing problem, because most monetary assets yield interest. Thus, an interest yielding monetary asset is a joint product: a durable good providing a monetary service ow and a nancial asset yielding a return. The currency equilivant index provides an elegant solution, but it does so by making strong assumptions about expectations of future monetary service ows. These assumptions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
0
15
0
Order By: Relevance
“…In his paper, Barnett showed that under certain assumptions the Economic Stock of Money (ESM), which is defined to be the present value of the monetary service flows yielded by current and future holdings of monetary assets, reduces to the CE. However, Barnett et al (2005Barnett et al ( , 2008 found that these assumptions make the CE a biased measure of the ESM.…”
mentioning
confidence: 95%
“…In his paper, Barnett showed that under certain assumptions the Economic Stock of Money (ESM), which is defined to be the present value of the monetary service flows yielded by current and future holdings of monetary assets, reduces to the CE. However, Barnett et al (2005Barnett et al ( , 2008 found that these assumptions make the CE a biased measure of the ESM.…”
mentioning
confidence: 95%
“…Moreover, simple-sum methodology ignores the fact that an interest yielding monetary asset is a joint product of a monetary and an investment asset. Barnett, Chae, and Keating (2005) and Barnett, Keating, and Kelly (2008) argue that because of this confounding, the official monetary aggregates confound the money stock with the present value of the investment yield returned by monetary assets, and thus significantly over-state the money stock. Kelly (2009) showed that this confounding causes simple-sum aggregates to fail to capture the true relationship between the economic money stock and interest rates.…”
Section: Iwhmentioning
confidence: 99%
“…These problems can only be addressed by carefully measuring money using 1 This includes the seminal contributions of Gordon and Leeper (1994), Leeper, Sims, and Zha (1996) Bernanke andMihov (1998), Christiano, Eichenbaum, andEvans (1996) and Christiano, Eichenbaum, and Evans (1999). 2 See, e.g., Barnett and Serletis (2000), Barnett, Chae, and Keating (2005), Barnett, Keating, and Kelly (2008), Barnett and Chauvet (2011), Kelly (2009), and Kelly, Barnett, and Keating (2011 The remainder of the paper is structured as follows. Since the use of Divisa money is quite unusual in this literature, sections two and three will start by introducing the dataset and giving a brief descriptive analysis of the core developments.…”
mentioning
confidence: 99%
“…Barnett, Keating, and Kelly (2008) and Barnett, Chae, and Keating (2005) formulate ESM under uncertainty as…”
Section: Denition Of the Current Stock Of Moneymentioning
confidence: 99%
“…Specically, I will show that the simple sum monetary aggregate confounds the current stock of money with the investment stock of money and that this confounding leads the simple sum monetary 1 See Hafer et al (2007) for a brief listing. 2 See Barnett and Serletis (2000), Barnett, Chae, and Keating (2005), Barnett, Keating, and Kelly (2008) for example. 2 aggregate to report an articially smooth monetary stock.…”
Section: Introductionmentioning
confidence: 99%